Effectiveness of a short-term multimodal prehabilitation program in adult patients awaiting selective cardiac surgery: study protocol for an open-label, pilot, randomized controlled trial - Gao, Wen; Li, Hongyan; Chen, Yuaner; Zhang, Yuping; Zhang, Mao; Jin, Jingfen (Frontiers in Cardiovascular Medicine, 2023)
Background Prehabilitation has been demonstrated to positively impact postoperative recovery in patients undergoing selective cardiac surgery. However, the optimal modules included in prehabilitation programs are yet to be fully explored, as existing studies have primarily focused on exercise. This study will explore the effectiveness of a three-arm prehabilitation program among adult patients awaiting selective cardiac surgery. Methods and analysis A single-center, parallel-group randomized controlled trial will be conducted at the Second Affiliated Hospital of Zhejiang University School of Medicine (SAHZU). A total of 152 adult patients scheduled for elective cardiac surgery (coronary artery bypass grafting or valvular surgery) will be recruited from a tertiary teaching hospital. The patients will be randomly assigned to either the control group or the prehabilitation group. Patients assigned to the control group will receive standard care, which includes patient education and counseling as well as personal guidance on exercise, breathing, and coughing. Patients in the intervention group will be provided a multimodal prehabilitation program, including nutrition guidance, a diet journal, mindfulness training, and exercise guidance. The interventions will begin with home-based training and continue after hospital admission and before surgery. The primary outcome will be the perioperative 6-minute walk distance (6 MWD). The secondary outcomes will include preoperative readiness, postoperative recovery, and patient experience with the program. Discussion The purpose of the study is to examine whether a short-term multimodal prehabilitation program will be associated with improved preoperative readiness and postoperative outcomes. The findings of this study will provide evidence to support the development of a perioperative program aimed at enhancing patient recovery. Clinical Trial Registration www.ClinicalTrials.gov; identifier: NCT05503004.